Thermoelastic Anomaly of Iron Carbonitride Across the Spin Transition and Implications for Planetary Cores - Shengxuan Huang; Xiang Wu; Stella Chariton; Vitali Prakapenka; Shan Qin; Bin Chen (Geophysical Research Letters, 2024)
Abstract Carbon and nitrogen are considered as candidate light elements present in planetary cores. However, there is limited understanding regarding the structure and physical properties of Fe‐C‐N alloys under extreme conditions. Here diamond anvil cell experiments were conducted, revealing the stability of hexagonal‐structured Fe7(N0.75C0.25)3 up to 120 GPa and 2100 K, without undergoing any structural transformation or dissociation. Notably, the thermal expansion coefficient and Grüneisen parameter of the alloy exhibit a collapse at 55–70 GPa. First‐principles calculations suggest that such anomaly is associated with the spin transition of iron within Fe7(N0.75C0.25)3. Our modeling indicates that the presence of ∼1.0 wt% carbon and nitrogen in liquid iron contributes to 9–12% of the density deficit of the Earth's outer core. The thermoelastic anomaly of the Fe‐C‐N alloy across the spin transition is likely to affect the density and seismic velocity profiles of (C,N)‐rich planetary cores, thereby influencing the dynamics of such cores.